Bert Laeyendecker als docent - Engbersen, Godfried (Religie & Samenleving, 2022)
In this article the author deals with Laeyendecker as teacher at the Sociological Institute Leiden. He studied in that time at that institute. Laeyendecker was an outstanding teacher who was able to explain the richness of sociology’s theoretical pluralism, and to show convincingly that sociology is a thoroughly social phenomenon. He was a very gifted orator with which he could enchant the audience of students.